Pengaruh Model Mastery Learning Terhadap Kemampuan Pemecahan Masalah dan Kemampuan Literasi Matematis Kelas VII SMP - Sri Rezeki; Yahfizham Yahfizham; Rusi Ulfa Hasanah (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aimed to determine the effect of the Mastery Learning model on students’ problem-solving ability and mathematical literacy ability in seventh-grade junior high school students. This study employed a quantitative approach with a quasi-experimental design. The population consisted of all seventh-grade students totaling students. The sample used was total sampling, namely class VII-A as the experimental class consisting of  students and class VII-B as the control class consisting of  students. Data were collected through pretest and posttest instruments. The results showed that the Mastery Learning model had an effect on improving students’ problem-solving ability and mathematical literacy ability. Based on the N-Gain results, the average problem-solving ability in the experimental class was , which was higher than the control class at . Meanwhile, the mathematical literacy ability in the experimental class obtained an average score of , while the control class obtained . Hypothesis testing showed that the problem-solving ability had a one-tailed significance value of . The mathematical literacy ability showed a one-tailed significance value of . Therefore, it can be concluded that the Mastery Learning model had a significant effect on both problem-solving ability and mathematical literacy ability.